Dogtrot-Galatia, Barton County - Schmidt, Keari (Kansas State University, The Chapman Center for Rural Studies, 2011)
Galatia—originally Dogtrot—provided a center-place town for many dispensed people in Barton County. Some former residents still recall the bustling streets of this prairie community. In preserving its history, we also preserve the history of Kansas and other similar communities.
Keari Schmidt, “Dogtrot-Galatia, Barton County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/49.
Keywords: Barton County; Dogtrot; Fairview Cemetery; Galatia; German Immigrants; Great Bend